Translanguaging as a Pedagogical Strategy in Bilingual Primary Classrooms in Nigeria - Olusegun Oladele Jegede (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2024)
This study explored translanguaging in bilingual classrooms, focusing on its impact on student engagement, language proficiency, and academic performance while examining teachers' perceptions and their implementation challenges. Using a mixed-methods approach, the study gathered qualitative data through semi-structured interviews and classroom observations and quantitative data through surveys and standardized tests involving 50 teachers and 250 students across five bilingual primary schools. The findings revealed that translanguaging practices fostered improved student engagement, comprehension, and academic performance, with significant gains in language proficiency. Teachers held positive perceptions of translanguaging, noting its potential to facilitate better learning, although they also pointed out challenges such as limited teacher training, rigid curricula, and resistance to change. The study revealed that translanguaging had a transformative impact on academic outcomes, especially in language subjects, but faced barriers to consistent implementation. The study concluded that translanguaging practices significantly enhance student engagement, comprehension, and academic performance but face challenges such as limited teacher training and curriculum rigidity, necessitating policy reforms and professional development for effective implementation. This study contributes valuable insights into the effectiveness of translanguaging in Nigerian bilingual classrooms, revealing its positive impact on academic outcomes and the need for curriculum reform, teacher training, and policy adaptation to support its implementation.